A Tauhidic Phenomenology Study of the Meaning of Profit - Mazidatul Faizzah; Ajeng Tita Nawangsari; Mochammad Ilyas Junjunan (International Journal of Religious and Cultural Studies, 2023)
This study seeks to investigate the meaning of profit as expressed in a local trader stall, which sells a set of food, consisting seventeen types of side dishes, and drinks for a very low price while applying Islamic values in its selling practices. This research employed a qualitative study with a phenomenological tauhid approach as its analytical tool. Data collection for this research was obtained through in-depth interviews. The study results indicate that the owner of food stall considers the meaning of profit to be vast and not limited to financial or material gain. Profit can take the form of enjoyment, sufficiency, and the fulfillment of a servant's prayer by Allah SWT. This is different from the concept of profit in general, which is the difference between the total amount of revenue generated as a result of transactions and the total costs associated with that revenue.